2011
DOI: 10.4102/sajcd.v58i2.28
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a programme to support foundation-phase teachers to facilitate literacy

Abstract: Learners who do not develop adequate listening and language skills during their early years are at risk of academic failure and early drop-out. Future learning problems may be prevented by supporting these children in the foundation phase to overcome their developmental delays. A continued professional development (CPD) programme was developed to support foundation-phase teachers to facilitate literacy. The theoretical basis for the workshop material was the articulation between an auditory processing model, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In the second article based on the qualitative component, the author reported on the analyses of English language learners’ journal entries to determine the impact of literacy experiences as bilingual writers (Danzak, 2011b ). Similarly, Wium ( 2010 ) developed a support programme for foundation-phase teachers to facilitate literacy and numeracy skills, which was evaluated using a variety of quantitative and qualitative methods. QUAN data were collected with questionnaires from 96 participants to determine how the programme was implemented in two different contexts, together with portfolio assessments.…”
Section: Critical Appraisal Of Mixed-methods Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second article based on the qualitative component, the author reported on the analyses of English language learners’ journal entries to determine the impact of literacy experiences as bilingual writers (Danzak, 2011b ). Similarly, Wium ( 2010 ) developed a support programme for foundation-phase teachers to facilitate literacy and numeracy skills, which was evaluated using a variety of quantitative and qualitative methods. QUAN data were collected with questionnaires from 96 participants to determine how the programme was implemented in two different contexts, together with portfolio assessments.…”
Section: Critical Appraisal Of Mixed-methods Researchmentioning
confidence: 99%
“…Controversies and challenges may occur in the conceptualisation stage of research (in providing a rationale for the mixing of methods), the operationalisation stage (how the methods will be used) or the synthesis stage where the findings of various methods used are interpreted. Teddlie and Tashakkori ( 2003 ) pointed to the following controversies which have also been experienced by some South African studies: (1) the nomenclature and basic definitions used in MMR remain to be disputed, (2) the use of MMR, (3) paradigms underpinning MMR, (4) issues related to the design of MMR (Schütte, 2016 ), (5) inferences derived from MMR (Wium, 2010 ) and (6) logistics when conducting MMR (Wium & Louw, 2011 ).…”
Section: Critical Review Of Mixed-methods Researchmentioning
confidence: 99%
“…Research conducted by Sims and Lonigan (2013), as well as by Spangler and Slate (2012), emphasises the fact that training programmes need to address gaps in teachers’ overall knowledge of ADHD and emergent literacy, including awareness, skills, motivation, values, accountability and attitudes (Wium, 2010). The training of teachers will consequently affect learners, helping them to succeed both socially and academically (Murray, 2009; Perold et al, 2010; Procaccini, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although previous studies in the South African context described teachers’ knowledge of ADHD (Perold et al, 2010), none reported on teachers’ ability to identify and manage barriers to learning, such as ADHD and co-morbid conditions. Two local programmes aimed at Foundation Phase teachers only addressed either ADHD (Wessels, 2011) or emergent literacy (Wium, 2010). Several local researchers pointed out that quality support programmes and guidelines should be developed for teachers in the South African context (Amod et al, 2013; Olivier, Anthonissen & Southwood, 2010; Perold et al, 2010; Wium, 2010), as there is a paucity of research on the development of support programmes for preschool teachers in the identification and management of ADHD and co-morbid conditions such as emergent literacy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation